Diversity and dynamics of endosymbionts in a single population of sweet potato weevil, Cylas formicarius (Coleoptera: Brentidae): a preliminary study. Issue 2 (13th April 2023) - Xu, Jin; Tan, Jian-Bin; Li, Yi-Dan; Xu, Yuan-Hao; Tang, An; Zhou, Hong-Kai; Shi, Pei-Qiong
Abstract: Endosymbionts live symbiotically with insect hosts and play important roles in the evolution, growth, development, reproduction, and environmental fitness of hosts. Weevils are one of the most abundant insect groups that can be infected by various endosymbionts, such as Sodalis, Nardonella, and Wolbachia . The sweet potato weevil, Cylas formicarius (Coleoptera: Brentidae), is a notorious pest in sweet potato ( Ipomoea batatas L.) cultivation. Currently, little is known about the presence of endosymbionts in C. formicarius . Herein, we assessed the endosymbiont load of a single geographic population of C. formicarius . The results showed that Nardonella and Rickettsia could infect C. formicarius at different rates, which also varied according to the developmental stages of C. formicarius . The relative titer of Nardonella was significantly related to C. formicarius developmental stages. The Nardonella -infecting sweet potato weevils were most closely related to the Nardonella in Sphenophorus levis (Coleoptera, Curculionidae). The Rickettsia be identified in bellii group. These results preliminarily revealed the endosymbionts in C. formicarius and helped to explore the diversity of endosymbionts in weevils and uncover the physiological roles of endosymbionts in weevils.